Intranasal Immunization Enhances Clearance of Nontypeable Haemophilus influenzae and Reduces Stimulation of Tumor Necrosis Factor Alpha Production in the Murine Model of Otitis Media - Sabirov, Albert (American Society for Microbiology, 2001)
Nontypeable Haemophilus influenzae (NTHi) is a major pathogen causing otitis media (OM). One of the outer membrane proteins of NTHi, P6, is a common antigen to all strains and is considered a candidate for mucosal vaccine. We have previously reported that intranasal immunization with P6 and cholera toxin (CT) could induce P6-specific immunoglobulin A (IgA) antibodies in the middle ear. In the present study, we assessed the effect of intranasal immunization for the protection against NTHi-induced OM. Mice were immunized intranasally with P6 and CT as an adjuvant on days 0, 7, and 14. Control mice were given phosphate-buffered saline (PBS) without antigen. One week after the final immunization, a suspension of live NTHi (10(7) CFU) was injected into the tympanic cavity to induce experimental OM. On days 3 and 7 after bacterial challenge, mice were killed and middle ear effusions (MEEs) were collected. All immunized mice showed elevated titers of P6-specific antibodies in MEEs. The rank order of specific antibody included, from highest to lowest levels, IgG, IgA, and IgM. In addition, immunized mice showed enhanced clearance of NTHi from the middle ear and the number of NTHi in MEEs of immunized mice was reduced by 97% on day 3 and by 92% on day 7 after bacterial challenge relative the number in the MEEs of control mice. The protective effect of intranasal immunization on the incidence of NTHi-induced experimental OM was evident on day 7 after challenge. By day 7, the number of MEEs in immunized mice was 64% less than that in control mice and the incidence of NTHi culture-positive MEEs in immunized mice was 56% less than that in control mice. Less stimulation of tumor necrosis factor alpha (TNF-α) production in the middle ear was evident on day 3 after challenge. Immunized mice showed lower concentrations of TNF-α in MEEs. These results indicate that intranasal immunization affords protection against experimental OM as evidenced by enhanced clearance of NTHi and less stimulation of TNF-α production in the middle ear. These findings suggest that a nasal vaccine might be useful for preventing OM.